2020
DOI: 10.1177/2050313x20936098
|View full text |Cite
|
Sign up to set email alerts
|

Rare case of meningitis due to an emerging pathogen Chryseobacterium indologenes

Abstract: Chryseobacterium indologenes is a non-glucose fermenting Gram-negative bacteria widely distributed in nature. It has been found to cause a variety of infections like nosocomial pneumonia, bacteremia and wound infections usually in immunosuppressed patients and those with indwelling devices. The organism is resistant to a significant number of the commonly prescribed broad spectrum antibiotics. We report a rare case of meningitis due to C. indologenes in a patient diagnosed with medulloblastoma and hydrocephalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Although some studies have reported that C. indologenes remains susceptible to trimethoprim/sulfamethoxazole, quinolones, minocycline, cefepime, ceftazidime, piperacillin-tazobactam, and rifampin ( 10 , 18 , 81 , 82 ), our strain was resistant not only to piperacillin–tazobactam, ciprofloxacin, cefepime, and ceftazidime but also to colistin and tigecycline. Our findings are in accordance with other studies ( 3 , 9 , 24 ) that show an increasing trend in resistance of C. indologenes against most commonly used antimicrobial agents.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although some studies have reported that C. indologenes remains susceptible to trimethoprim/sulfamethoxazole, quinolones, minocycline, cefepime, ceftazidime, piperacillin-tazobactam, and rifampin ( 10 , 18 , 81 , 82 ), our strain was resistant not only to piperacillin–tazobactam, ciprofloxacin, cefepime, and ceftazidime but also to colistin and tigecycline. Our findings are in accordance with other studies ( 3 , 9 , 24 ) that show an increasing trend in resistance of C. indologenes against most commonly used antimicrobial agents.…”
Section: Discussionsupporting
confidence: 93%
“…Although the clinical significance and pathogenicity of C. indologenes are not well established (17,18), C. indologenes is known to be naturally resistant to a wide variety of antibiotics including not only aminoglycosides, tetracyclines, chloramphenicol, macrolides, aminopenicillins, clindamycin, teicoplanin but also first-generation cephalosporins, aztreonam, ticarcillin-clavulanate, and carbapenems (10,(19)(20)(21). The most potent drugs reported against C. indologenes are quinolones (gatifloxacin and levofloxacin), minocycline, and trimethoprimsulfamethoxazole (18,22,23); however, many studies show an alarming trend in resistance to those antibiotics (3,9,24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No hemolytic properties were observed. The hemolytic activities of Bacillus [Dabiré et al, 2022], Chryseobacterium [Sud et al, 2020], Mycobacterium [Augenstreich et al, 2020], and Stenotrophomonas genera [Peters et al, 2020] were reported. However, only Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…C. indologenes was first isolated in 1993 from a tracheal aspirate in a patient with ventilator-associated pneumonia [ 2 3 ]. Although it rarely causes infections, manifestations such as bacteremia, pneumonia, intra-abdominal infection, skin and soft tissue infection, urinary tract infection, meningitis, keratitis, and catheter-related infections have been reported [ 4 5 6 7 8 9 10 11 12 13 14 15 16 ]. It can cause serious disease, especially in immunocompromised and critically ill patients and sometimes associated with prolonged indwelling devices ( e.g.…”
Section: Introductionmentioning
confidence: 99%